Faktor-Faktor Yang Mempengaruhi Opini Going Concern Pada Saat Pandemi Covid 19 - Evi Yana Hasmi; Usep Syaipudin; Widya Rizki Eka Putri (E-journal Field of Economics, Business and Entrepreneurship (EFEBE), 2022)
Going concern becomes a problem that must be addressed by management in managing the company, so that the company continue to operate for a long time especially during a pandemic where the economic situation is unstable and makes the going concern company's disrupted. This study aims to analyze the Effect of company growth, financial condition, opinion shopping and previous year’s audit opinion to the acceptance of going concern audit opinion during covid 19 pandemic . The sampling technique used in this study is purposive sampling with a total sample of 48 infrastructures companies listed on the Indonesia Stock Exchange during pandemic the period of research year 2019-2020. Hypothesis testing of this research is done by logistic regression analysis. The result of this study shows that company's growth have no effect significant on the going concern audit opinion, opinion shopping have no effect significant on the going concern audit opinion, financial condition have no effect significant on the going concern audit opinion, the previous year audit opinion have effect significant on the going concern audit opinion.